Environmental management accounting in the Middle East and North Africa region: Significance of resource slack and coercive isomorphism. (10th September 2020) - Asiri, Nasser; Khan, Tehmina; Kend, Michael
Abstract: The Middle East and North Africa (MENA) region is suffering from serious environmental issues, which are caused mainly by industrial and non-financial business activities. Implementing environmental management accounting (EMA) will help businesses manage environmental issues better and improve how they treat the environment. The key motivation for undertaking this study is that earlier research reported a poor level of environmental accounting practices by firms in the MENA region. These studies documented the necessity to develop a better understanding of EMA practices and the factors that influence their employment. Based on the new institutional sociology (NIS) perspective of institutional theory and resource slack theory, this study examines the influence of technological capabilities, environment-focused human resources management (EFHRM) and institutional isomorphism, specifically on the extent to which EMA practices are implemented in non-financial listed firms from eight MENA countries. These countries are Saudi Arabia, United Arab Emirates, Kuwait, Oman, Qatar, Bahrain, Jordan and Egypt. A web-based survey approach was utilised; and the data was analysed through structural equation modelling (SEM). The findings indicated an overall poor widespread of the use of EMA practices in the selected firms as perceived by the participants. Also, the findings suggest that technological capabilities, EFHRM and coercive isomorphism positively and significantly influence how EMA practices are implemented. Coercive pressures, technological and human resources are affecting the extent of EMA use in this study's sample, but not to a great extent. Hence, coercive pressures should be maximised by regulatory bodies in the selected MENA countries in order for EMA practices to be widely accepted. Furthermore, governments should facilitate the outsourcing of experts who can help with implementing EMA practices. It means collaborating with non-government partners, such as accounting associations, industry associations, research & consulting firms and educational institutions. These kinds of collaborations can lead to better support for environmental management and EMA, thus instituting the required educational programs and training to enhance employees' awareness of EMA practices that include the role of technology.